PENGARUH KEPATUHAN DAN MOTIVASI PENDERITA TB PARU TERHADAP TINGKAT KESEMBUHAN PENGOBATAN DI PUSKESMAS TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2017 - Reni Aprinawaty Sirait; Imelda J Verawati Lubis (Jurnal Penelitian Kesmasy, 2018)
Tuberculosis (TB) is one of the infectious disease remains a significant health problem forpeople the world till now, including Indonesia. Tanjung Morawa Health Center is clinicthat the lowest cure rate of 34 health centers in Deli Serdang district. The number ofpatients with Pulmonary TB positive BTA at Deli Serdang district by the Year 2014 manyas 142 people with cure rate 75,79% In year 2015, there were 124 patients withPulmonary TB positive BTA but cure rate 63,5%.. This means decreasing of cure ratein Deli Serdang district and did not reach the target yet was set at least 85%. This type ofresearch using explanatory research aims to explain the effect of adherence andmotivation cure level of pulmonary tuberculosis treatment at Tanjung Morawa . Thepopulation were all patients with positive BTA pulmonary TB with a sample size of 21people. The results of bivariat statistic test showed variables which influence treatment ofPulmonary TB cure rate, patient compliance (p=0.002), the family support/PMO(p=0.003) and staff support (p=0.008). For increase TB patients awareness need IECabout pulmonary tuberculosis diseases, extension or counseling patients that patientsmore understand about their diseases and responsible on their recovery.